Differential recruitment of brain circuits during fear extinction in non-stressed compared to stress resilient animals - Jiah Pearson-Leary; Alexander P. Abramenko; Valerie Estela-Pro; Elizabeth Feindt-Scott; Jason Yan; Abigail Vigderman; Sandra Luz; Debra Bangasser; Richard Ross; Leszek Kubin; Seema Bhatnagar (Scientific Reports, 2024)
Abstract Dysfunctional fear responses in post-traumatic stress disorder (PTSD) may be partly explained by an inability to effectively extinguish fear responses elicited by trauma-related cues. However, only a subset of individuals exposed to traumatic stress develop PTSD. Therefore, studying fear extinction deficits in animal models of individual differences could help identify neural substrates underlying vulnerability or resilience to the effects of stress. We used a rat model of social defeat in which rats segregate into passively and actively coping rats. In previous work, we showed that passively coping rats exhibit disruptions in social interaction whereas actively coping rats do not display behaviors differently from controls, indicating their resilience. Here, adult male rats exposed to 7 days of social defeat were tested for fear extinction, retention of extinction, and persistence of retention using contextual fear and ethologically-relevant fear tests. Passively coping rats exhibited elevated freezing in response to the previously extinguished context. Analyses of cFos expressing cells across select brain regions showed high correlations within dorsal hippocampal subregions, while passively coping rats had high correlations between the dorsal hippocampus CA1 and the central and basolateral subregions of the amygdala. Importantly, although control and actively coping rats showed similar levels of behavioral extinction, there was little similarity between activated structures, suggesting stress resilience in response to chronic social defeat involves an adaptive differential recruitment of brain circuits to successfully extinguish fear memories.